Unveiling the Hybrid Genome Structure of Escherichia coli RR1 (HB101 RecA+) - Jeong, Haeyoung; Sim, Young Mi; Kim, Hyun Ju; Lee, Sang Jun (Frontiers in Microbiology, 2017)
There have been extensive genome sequencing studies for Escherichia coli strains, particularly for pathogenic isolates, because fast determination of pathogenic potential and/or drug resistance and their propagation routes is crucial. For laboratory E. coli strains, however, genome sequence information is limited except for several well-known strains. We determined the complete genome sequence of laboratory E. coli strain RR1 (HB101 RecA+), which has long been used as a general cloning host. A hybrid genome sequence of K-12 MG1655 and B BL21(DE3) was constructed based on the initial mapping of Illumina HiSeq reads to each reference, and iterative rounds of read mapping, variant detection, and consensus extraction were carried out. Finally, PCR and Sanger sequencing-based finishing were applied to resolve non-single nucleotide variant regions with aberrant read depths and breakpoints, most of them resulting from prophages and insertion sequence transpositions that are not present in the reference genome sequence. We found that 96.9% of the RR1 genome is derived from K-12, and identified exact crossover junctions between K-12 and B genomic fragments. However, because RR1 has experienced a series of genetic manipulations since branching from the common ancestor, it has a set of mutations different from those found in K-12 MG1655. As well as identifying all known genotypes of RR1 on the basis of genomic context, we found novel mutations. Our results extend current knowledge of the genotype of RR1 and its relatives, and provide insights into the pedigree, genomic background, and physiology of common laboratory strains.